2017
DOI: 10.1161/atvbaha.116.308109
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genetic Variants Linking Protein C and Lipoprotein Metabolism

Abstract: Objective Previous studies have identified common genetic variants in four chromosomal regions that together account for 14–15% of the variance in circulating levels of protein C. To further characterize the genetic architecture of protein C, we obtained denser coverage at some loci, extended investigation of protein C to low frequency and rare variants, and searched for new associations in genes known to influence protein C. Approach and Results Genetic associations with protein C antigen level were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…From our systematic literature review of haematological traits we obtained published GWAS summary statistics for 36 blood cell traits and 49 haemostasis traits from 27 publications involving over 375 000 individuals (Supplementary Table 1) (Barbalic et al , 2010; Johnson et al , 2010; Smith et al , 2010, 2011; Athanasiadis et al , 2011; Lovely et al , 2011; Paré et al , 2011; Edelstein et al , 2012; Huang et al , 2012, 2014; Oudot-Mellakh et al , 2012; de la Morena-Barrio et al , 2013; Williams et al , 2013; Ma et al , 2014; Rocanin-Arjo et al , 2014; de Vries et al , 2015, 2016; Tang et al , 2015; Astle et al , 2016; van Loon et al , 2016; Dennis et al , 2017; Pankow et al , 2017; Sennblad et al , 2017; Kanai et al , 2018; Olson et al , 2018; Stanne et al , 2018; Sun et al , 2018). Figures 2 and 3 summarize the direction and magnitude of the association estimates for each haematological trait with each stroke subtype, with stronger associations indicated by darker colours (red in the positive direction and blue in the negative direction) and asterisks to indicate the level of statistical significance.…”
Section: Resultsmentioning
confidence: 99%
“…From our systematic literature review of haematological traits we obtained published GWAS summary statistics for 36 blood cell traits and 49 haemostasis traits from 27 publications involving over 375 000 individuals (Supplementary Table 1) (Barbalic et al , 2010; Johnson et al , 2010; Smith et al , 2010, 2011; Athanasiadis et al , 2011; Lovely et al , 2011; Paré et al , 2011; Edelstein et al , 2012; Huang et al , 2012, 2014; Oudot-Mellakh et al , 2012; de la Morena-Barrio et al , 2013; Williams et al , 2013; Ma et al , 2014; Rocanin-Arjo et al , 2014; de Vries et al , 2015, 2016; Tang et al , 2015; Astle et al , 2016; van Loon et al , 2016; Dennis et al , 2017; Pankow et al , 2017; Sennblad et al , 2017; Kanai et al , 2018; Olson et al , 2018; Stanne et al , 2018; Sun et al , 2018). Figures 2 and 3 summarize the direction and magnitude of the association estimates for each haematological trait with each stroke subtype, with stronger associations indicated by darker colours (red in the positive direction and blue in the negative direction) and asterisks to indicate the level of statistical significance.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed information on GWAS genotyping, quality control and imputation can be found elsewhere. [ 24 ] Imputation quality for the SNPs included in this study was good (quality score = 0.84–1.0 with a mean of 0.99). Additionally, 10 principal components of population stratification based on the GWAS data were generated by EIGENSTRAT[ 25 ] to reflect the population structure of the ARIC participants.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, a Mendelian randomization experiment in 10 778 white and 3190 black participants in the ARIC study (Atherosclerosis Risk in Communities) found that variants in the CELSR2-PSRC1-SORT1 region on chromosome 1 influenced circulating protein C levels, thus indicating a possible genetic link between lipoprotein metabolism and hemostasis. 13 Finally, a Mendelian randomization experiment by Coassin et al 14 found that genetic determinants of low HDL-C (high-density lipoprotein cholesterol) levels were not associated with worsened renal function (ie, estimated glomerular filtration rate), thus demonstrating that the relationship was not causal in nature.…”
Section: Statistical Genetic Associations With Vascular and Related Tmentioning
confidence: 99%